Isolasi dan Seleksi Bakteri Proteolitik Asal Limbah Cair Tahu Sebagai Dasar Penentuan Agen Pembuatan Biofertilizer - Muhammad Asril; Sovia Santi Leksikowati (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2019)
Liquid tofu waste has the effect of damaging the environment if treated poorly. The waste contains a reasonably high protein so that it can be used as a substrate for isolation of proteolytic bacteria. Proteases produced by proteolytic bacteria can hydrolyze proteins in liquid tofu waste. The results of protein hydrolysis are amino acids in the form of nitrogen. The nitrogen can be used by plants for nutritional growth so that bioconversion products from proteolytic bacteria can be used as biofertilizers. The purpose of this study was to isolate and select potential proteolytic isolates from tofu liquid waste, which could be used as biofertilizer agents. The method used was bacterial isolation, proteolytic activity test, potato decay test, hemolysis test, and antagonism test among isolates. The results showed that there were two potential isolates from 28 isolates that had been successfully isolated, namely BLT-12 and BLT 21 with each Proteolytic Index of 3.20 and 3.16, respectively. The two isolates were gram-positive in the form of basil, did not have hemolysis activity, could not decompose potatoes so that they did not have a pathogenic effect on the test plants and did not have antagonistic properties between the two others. Therefore, BLT 12 and BLT 21 isolates can be used as candidates for potential isolates of biofertilizer agents.